Bestek : Prijsvraag 1998. - ter Molen, Johan R. (Rotterdam : Museum Boijmans Van Beuningen, 1998)
de Buck, Siegfried ; Lucas, Arjen ; van Kouswijk, Manon ; van Dissel, Fleur ; Accessory in 't Veld & Partners ; Barteling, Simon ; Anderton, Simon ; van Baalen, Wouter ; Crooijmans, Marlies ; Artis Causa ; Schumacher, Gabri
boek